Acyloxyphosphonium versus Aminophosphonium Intermediates: Application to the Synthesis of N‐Acylbenzotriazoles. Issue 32 (9th October 2014) - Duangkamol, Chuthamat; Wangngae, Sirilak; Pattarawarapan, Mookda; Phakhodee, Wong
Abstract: In attempts to convert carboxylic acids directly into N ‐acylbenzotriazoles by using Ph3 P/I2 as an acid‐activating system, the outcome of the reaction is reversed from no reaction to almost quantitative yield of the expected product simply by switching the order of the addition of the reagents to the presumed acyloxyphosphonium intermediate. If triethylamine was present before treatment with 1 H ‐benzotriazole, anhydride was always exclusively generated without a detectable amount of the expected product. However, if the base was applied after the addition of 1 H ‐benzotriazole, the reaction proceeded smoothly to afford N ‐acylbenzotriazoles in good to excellent yields within short reaction times. 31 P NMR spectroscopy revealed the presence of a benzotriazophosphonium species in preventing the formation of the anhydride by attack of the carboxylate anion at the acyl function of the acyloxyphosphonium salt. Abstract : In synthesizing N ‐acylbenzotriazoles by using Ph3 P/I2 as an acid activator, anhydride is exclusively generated upon adding Et3 N to the presumed acyloxyphosphonium intermediate before treatment with 1 H ‐benzotriazole (BtH). In the absence of base, benzotriazophosphonium iodide is predominantly formed, which rapidly reacts with carboxylate ions to afford N ‐acylbenzotriazoles in good to excellent yields.